Pengaruh Kualitas Pelayanan, Harga dan Promosi Terhadap Keputusan Siswa Memilih Pelatihan di LPK Hinode Mandiri Karanganyar (Survei pada Siswa LPK Hinode Mandiri Karanganyar) - Irine Mawar Rima Anggraeni; Retno Susanti (Teewan Journal Solutions, 2026)
LPK Hinode Mandiri Karanganyar is an educational and skills institution that focuses on Japanese language training to prepare students who want to study and work in Japan. The research question in this study is whether there is a significant influence of service quality, price, and promotion on students' decisions to choose training at LPK Hinode Mandiri Karanganyar. This study aims to analyze the significance of the influence of service quality, price, and promotion on students' decisions to choose training at LPK Hinode Mandiri Karanganyar. The usefulness of this study is as a basis for consideration and input for LPK Hinode Mandiri Karanganyar, as well as a reference for future research using the same or different variables of service quality, price, and promotion with phenomena that are relevant in the future. The research hypothesis is that service quality, price, and promotion are positively and significantly influential on students' decisions to choose LPK Hinode Mandiri Karanganyar. This study uses a survey method conducted on students who have chosen and registered for training at LPK Hinode Mandiri Karanganyar from 2024 to April 2025. The required data includes the profile, vision, and mission of LPK Hinode Mandiri Karanganyar, the number of students, student responses, respondents' answers regarding service quality, price, promotions, and decision-making. The data source is primary data. Data collection techniques include questionnaires and direct observation. The sampling technique uses a saturated sampling approach with 50 respondents. Data analysis techniques use the SEM method with outer model testing, inner model testing, and hypothesis testing using the SmartPLS 3.0. Outer model test showed that the convergent validity of all questionnaire items was above 0.70, the discriminant validity with the HTMT criterion was less than 1, and the composite reliability value of each variable was greater than 0.70. Therefore, it can be concluded that all questionnaire items are valid and reliable. The results of the inner model test consist of an R2 test value of 0.684, meaning that the decision to choose variable can be explained by the variables of service quality, price, and promotion by 68.4%, while the remaining 31.6% is influenced by other variables outside this research model. The Q2 value is greater than 0, indicating that the variables of service quality, price, and promotion can serve as predictive relevance for the decisionto choose variable. The GoF test yields an SRMR value of 0.091 < 0.1, indicating that the model is increasingly fit, and an NFI value of 0.694 within the range of 0–1, indicating that the model is fit. The hypothesis test shows a p-value of 0.001, indicating that service quality has a positive and significant effect on the decision to choose, price has a p-value of 0.212, indicating that price has a positive but insignificant effect on the decision to choose, and promotion has a p-value of 0.805, indicating that promotion has a positive but insignificant effect on the decision to choose.